Peran Arsiparis Dalam Pengumpulan Barang Bukti Tindak Pidana Korupsi - Sukronie, Sukronie (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2025)
Corruption is an extraordinary crime that threatens development and public trust. In the process of handling corruption, the collection of evidence is a vital element. Archives as one form of authentic evidence have strategic value in the law enforcement process, especially in proving corruption. Archivists, as functional personnel who have competence in the field of archiving, play an important role in managing, securing, and providing archives that can be used as evidence in the legal process. This study aims to examine the role of archivists in supporting the collection of evidence in corruption cases, as well as the challenges faced in practice, and to examine in depth how the strategic role of archivists is in supporting the process of proving corruption cases, both at the investigation, inquiry, and trial stages. This study uses a descriptive qualitative method through literature studies and interviews with archiving practitioners and law enforcers. The results of the study show that the involvement of archivists in dynamic archive management, document authentication, and forensic assistance of archives greatly determines the success of handling corruption cases.